2021
DOI: 10.1111/aogs.14054
|View full text |Cite
|
Sign up to set email alerts
|

Maternal N‐acetyl‐cysteine prevents neonatal brain injury associated with necrotizing enterocolitis in a rat model

Abstract: Introduction Preterm infants with necrotizing enterocolitis (NEC) are at increased risk of cerebral injury and neurodevelopmental dysfunction. N‐acetyl‐cysteine (NAC) is a known anti‐inflammatory and antioxidant agent. Currently, there is no prophylactic treatment in clinical use to prevent NEC and its neurodevelopmental sequelae. We sought to determine whether brain inflammation/apoptosis accompanies NEC systemic inflammation, and whether it can be attenuated by maternal NAC treatment during pregnancy and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Our novel nding that NAC administered to either dams or offspring decreased TLR-4 protein levels in offspring ileum is of great importance. These ndings are consistent with reports of decreased NEC observed in previous studiesfollowing NAC treatment (Zmora et al 2020;Zmora et al 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our novel nding that NAC administered to either dams or offspring decreased TLR-4 protein levels in offspring ileum is of great importance. These ndings are consistent with reports of decreased NEC observed in previous studiesfollowing NAC treatment (Zmora et al 2020;Zmora et al 2021).…”
Section: Discussionsupporting
confidence: 93%
“…We further demonstrated that the decrease in brain TLR-4 following NAC was associated with increase in brain antioxidant glutathione levels, potentially enabling the brain to cope with increased oxidative stress and thus to decrease the brain injury. N-acetyl cysteine, a known anti-in ammatory and anti-oxidative agent, is considered safe for use during pregnancy (class B) (Zmora et al 2021). NAC's therapeutic properties stem from its action on the cystine-glutamate antiporter system and as an antioxidant to regulate the neuroin ammatory response (Dean et al 2011;Durieux et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal inflammation is known to adversely affect the processes of maturation in the immune and nervous systems during a critical period of development [87][88][89]. Systemic and brain inflammation in various prenatal and neonatal conditions including chorioamnionitis, sepsis, meningitis, and bronchopulmonary dysplasia, have been shown to be associated with neonatal brain injury and worse developmental outcomes [90,91]. NEC is known to involve both local and systemic inflammation.…”
Section: Inflammationmentioning
confidence: 99%
“…In mice with NEC, the activated microglia were found to be distributed in regions of the brain where myelination deficits were most evident, including the hippocampus, frontal cortex, and midbrain [2, 33]. Activation of microglia correlated with an accumulation of ROS and increased brain gene expression and protein levels of markers of inflammatory signaling and injury including IL-6, IL-1, TNFa , NF-kB, nNOS, caspase 3, and lipocalin-2 (Lcn2) [2, 33, 90]. In further support of the role of microglia in brain injury, attenuation of microglial activation in a mouse model of NEC resulted in significant reduction of ROS accumulation and prevented a decrease in myelin basic protein (Mbp) expression, loss of pre-OLs, and neurocognitive impairments, as evidenced by the performance on the Y-maze and novel object recognition memory tests [2].…”
Section: Mechanism Of Brain Injurymentioning
confidence: 99%
“…NAC mechanisms of action include increased glutathione peroxidase levels, antioxidant effect by free-radical scavenging, inhibition of the activation of NF-κB, inhibition of TNF toxicity, NOS inhibition, and prevention of mitochondrial dysfunction [34]. We previously demonstrated that NAC has a protective effect on pups' brain damage in the Entero Colitis model (NEC) [35]. NEC model is based on pups' formula feeding thrice daily which induces intestinal inflammation complemented with hypoxia treatment.…”
Section: Discussionmentioning
confidence: 99%